2021
DOI: 10.3390/antiox10121896
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Constituents from the Leaves of Actinidia arguta with Antioxidant and α-Glucosidase Inhibitory Activity

Abstract: As the leaf of Actinidia arguta has shown antioxidant activity, a study was conducted to identify the active ingredients. Forty-eight compounds were isolated from the leaves of A. arguta through various chromatographic techniques. Further characterization of the structures on the basis of 1D and 2D NMR and MS data identified several aromatic compounds, including phenylpropanoid derivatives, phenolics, coumarins, flavonoids and lignans. Among them, five compounds were newly reported, naturally occurring, and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Hence, we propose that combining the use of ethanolic extract with a low dosage of synthetic drugs could be one of the alternative possibilities for treating hyperglycemia with minimal side effects. In the literature, Proenca et al [ 128 ], Ahn et al [ 129 ], and Etsassala et al [ 130 ] found that phenolic and flavonoid phytochemicals can limit α-glucosidase activity by inserting themselves into the active site of the enzyme and interacting with it in various ways, including by traditional hydrogen bonding and carbon–hydrogen bonding. It can be inferred that the ethanolic extract, which exhibits α-glucosidase inhibitory activity, obtained in this study might block the substrate-binding active site of the enzyme, thereby preventing the oligosaccharides from accessing the active site.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we propose that combining the use of ethanolic extract with a low dosage of synthetic drugs could be one of the alternative possibilities for treating hyperglycemia with minimal side effects. In the literature, Proenca et al [ 128 ], Ahn et al [ 129 ], and Etsassala et al [ 130 ] found that phenolic and flavonoid phytochemicals can limit α-glucosidase activity by inserting themselves into the active site of the enzyme and interacting with it in various ways, including by traditional hydrogen bonding and carbon–hydrogen bonding. It can be inferred that the ethanolic extract, which exhibits α-glucosidase inhibitory activity, obtained in this study might block the substrate-binding active site of the enzyme, thereby preventing the oligosaccharides from accessing the active site.…”
Section: Resultsmentioning
confidence: 99%
“…The free radical scavenging activity measurement utilizing DPPH was used to determine the antioxidant activity, as reported in the prior study [ 36 ]. The absorbance was determined using 550 nm as the wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant activities in different plant tissues can be significantly influenced by the type and structure of the active compounds present. The presence of specific compounds [43] in root tissues of the kiwiberry, such as terpenoids (e.g., 2α,3β-dihydroxyurs-12-en-28,30-olide, 12α-chloro-2α,3 β,23-tetrahydroxyolean-28-oic acid-13-lactone, and oleanolic acid) [44][45][46], flavonoids (e.g., (−)-epi-catechin, (+)-catechin, and Procyanidin B4) [47], phenolics (planchol A, B and isotachioside) [44], and other unique organic and volatile compounds, can explain the higher antioxidant activity in the roots compared to the leaves [48]. For example, oleanolic acid is a natural terpenoid known to function as a powerful antioxidant to scavenge free radicals and protect against oxidative stress [49,50].…”
Section: Antioxidant Activity In Vegetative Tissues Of Kiwiberry Cult...mentioning
confidence: 99%